Non-communicable disease and mental health care during the COVID-19 pandemic in South Africa: Perspectives from selected healthcare professionals and patients - Nasheeta Peer; Tshephang Mashiane; Michel Oris; Kibachio Mwangi; Sugitha Sureshkumar; Andre-Pascal Kengne (PLoS ONE, 2025)
Aim South Africa has a high burden of non-communicable diseases (NCDs) and experienced a high COVID-19 caseload, while the healthcare system was already overstretched. The aim of this study was to examine the perceptions and experiences of 1) healthcare professionals (HPs) of COVID-19 and NCD management, and the preparedness of health systems to provide NCD care, and 2) people living with NCDs (PLWNCDs) on the care they received, their mental health status and the availability of health information during the COVID-19 pandemic in South Africa. Methods We recruited a convenience sample of 1) HPs who worked in healthcare management, i.e., public health officials and healthcare workers who provided care and engaged with patients in any healthcare capacity, and 2) PLWNCDs with ≥1 NCD. Questionnaires comprised quantitative and some open-ended follow-up questions. SPSS was used to analyse the quantitative data, and content analysis with inductive reasoning was used to evaluate the open-ended questions. Results This cross-sectional study comprised 31 HPs and 79 PLWNCDs. The provision of COVID-19 care was perceived to be adequate by HPs while NCD care was poor with disruptions of services, including for emergency and specialised NCDs care. Strategies to care for non-COVID-19 illnesses during the pandemic were lacking. This would have serious long-term consequences for PLWNCDs and the healthcare system. Perceptions of inadequate NCD care were repeated by PLWNCDs; 49% felt they received ‘very little’ or no adequate care and 18% had a scheduled appointment cancelled. Further, many PLWNCDs (52%) felt anxious, lonely or frightened during the pandemic and 15% felt their mental health had deteriorated, but only a small proportion sought medical attention. The utility of digital health was positively perceived by both HPs and PLWNCDs and could contribute to better health provision during crises. Conclusions Policies are needed to ensure that NCD care will not be neglected during future crises and to encourage PLWNCDs to access healthcare services timeously during such periods. Potential strategies may utilise digital health apps to improve care and to address the mental healthcare needs of PLWNCDs.